Seven keys to unlock autism : making miracles in the classroom - Hall, Elaine, 1956- (Jossey-Bass, 2012)
This book are based on the unique, world-acclaimed approach used by Elaine Hall and Diane Isaacs of the Miracle Project, a fully inclusive socialization and communication program for children with autism and their typically developing peers and siblings.